Keterampilan Pembuatan Kerudung Praktis Pada Siswi SMP Islam Madinatul Ilmi - Yeni Sesnawati; Vivi Radiona Sofyani Putri (Universitas Persada Indonesia YAI, 2023)
The training on making practical headscarves aims to be able to provide skills and creativity forMadinatul Ilmi Islamic pupils in Muara Gembong Distric Bekasi Regency.This training activity was attendedby 15 participants which was carried out offline at the Islamic Middle School Madinatul Ilmi. The teachingmaterial provided includes basic knowledge about practical headscarves, tools and materials needed,creation in making practical headscarves, and sewing techniques applied. The training methods carried outwere lectures, demonstrations, and experiments in making practical headscarves. The results of the trainingshowed an increase in pupils’ knowledge and skills in making practical headscarves as a provision for pupilsto develop their abilities.